Combined family-based association and linkage analyses in families affected by attention-deficit hyperactivity disorder - Cristina M. Justice; Kwangmi Ahn; Benjamin Jung; Luke J. Norman; Gustavo Sudre; Wendy Sharp; Marine Bouyssi-Kobar; Saadia Choudhury; Stevi Gligorovic; Paul Kundzicz; Maria T. Acosta; Philip Shaw (Human Genetics, 2026)
Attention deficit hyperactivity disorder (ADHD) is one of the most prevalent and heritable of neurodevelopmental disorders. To characterize the genetic variants contributing to this heritability, we studied families with members affected by ADHD. Genome-wide array data were obtained on two cohorts: NHGRI Family Cohort (359 nuclear families,1538 individuals) and NCR Family Cohort (25 multigenerational and 132 nuclear families, 631 members). A meta-analysis of family-based association tests (FBAT) of the two cohorts identified three genome-wide significant associations, one upstream from TFRC , and two that were intronic to GSDME and to TRIM31 , with the last gene previously implicated in ADHD. Genes associated with ADHD (MAGMA, gene-based association P < 0.05) overlapped with genes implicated in ADHD by prior case/control genome-wide association studies. Meta-analyses of the linkage signals identified one significant linkage region (LOD > 3) on 19p13.2-13.11 that encompassed a genome-wide significant variant in the FBAT of the NHGRI Family Cohort (rs55741253, P = 2.68 × 10 − 8 ). Additionally, two of the five linkage regions that reached a LOD > 2 in our meta-analysis replicated significant linkages from prior studies (prior studies reporting 13 linkages with LOD > 3.0; hypergeometric test of overlapping linkage signals, P < 0.01). Using neuroimaging data from the NCR cohort, we found genes associated with ADHD overlapped with genes associated with the brain’s total surface area and a feature of functional connectivity, reflecting the interaction between the brain’s default mode and task positive networks. Such work begins to delineate the neural substrates of the discovered genetic associations with familial ADHD.

Assessing the efficacy of coral restoration along Florida’s coral reef under the chronic persistence of stony coral tissue loss disease - William C. Sharp; Kristene T. Parsons; Erinn M. Muller; Amanda Bourque; David S. Gilliam; Diego Lirman; Colin P. Shea; Joshua D. Voss; John H. Hunt (Frontiers in Marine Science, 2026)
Stony coral tissue loss disease (SCTLD) has caused unprecedented coral mortality across Florida’s Coral Reef (FCR) since 2014, raising concerns about whether coral restoration can succeed under chronic disease conditions and whether outplanting activities may increase disease transmission risk. As the disease transitioned from epizootic outbreak to enzootic persistence, we conducted a large-scale experimental outplanting to assess coral restoration efficacy under chronic SCTLD persistence and to evaluate the relative importance of SCTLD versus non-disease drivers of restoration outcomes. From May 2021 through April 2023, we outplanted 1,165 colonies of three SCTLD-susceptible species ( Montastraea cavernosa, Orbicella faveolata , and Pseudodiploria clivosa ) sourced from land-based facilities and in-water nurseries across six regions spanning FCR and monitored survival and disease incidence. Concurrent surveys of natural coral communities assessed whether outplanting activities affected local SCTLD prevalence. Probabilities of infection per monitoring interval remained <1-2% across all species, regions, and propagation sources throughout the monitoring period. Importantly, outplanting activities did not increase SCTLD prevalence in neighboring natural coral communities. In contrast to the low and relatively uniform disease incidence, variation in coral survival was strongly structured by ecological and operational factors. The overall coral colony survival rate at the end of the study was 77.3% but was influenced by reef stratum (inshore vs. offshore reefs), geographic region, and colony source. M. cavernosa and P. clivosa exhibited higher survival at inshore sites compared to offshore sites, whereas O. faveolata showed no consistent reef stratum effect on survival. Across FCR, survival varied spatially between regions independent of latitude, suggesting local environmental drivers. Colony source effects varied by species. M. cavernosa and P. clivosa from land-based facilities exhibited significantly lower survival than colonies from in-water nurseries, whereas O. faveolata showed no significant differences between propagation sources. Our results indicate that under SCTLD-enzootic conditions, restoration outcomes are shaped more strongly by habitat suitability, geographic context, and propagation-related factors than by SCTLD itself. These findings suggest that coral restoration can proceed within SCTLD-enzootic zones without increasing disease risk to neighboring coral communities or substantially elevating SCTLD-related mortality of outplanted colonies.

Impact of climate change on freshwater macronutrients and agricultural yields across Britain - Nathan Missault; Victoria A. Bell; David M. Cooper; Ryan T. Sharp; Andrew P. Whitmore; Alice E. Milne; Helen N. Davies (Journal of Environmental Management, 2026)

Rethinking land-use Strategies: A multi-objective analysis of combined sparing and sharing approaches applied across great britain - Imane El Fartassi; Ryan T. Sharp; Victoria A. Bell; Andrew P. Whitmore; Helen Metcalfe; Nathan Missault; John Redhead; David M. Cooper; Jonathan Storkey; Helen Davies; Theo Jackson; Kevin Coleman; et al. (Journal of Environmental Management, 2026)

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Perception of Body Fat and Body Fat Percentages Among Female College Students - M. Schmidt; D. Beeson; S. Keck; T. Pulver; M. Scott; N. Sharp; E. Weaver; C. Lyman; A. Grady (Journal of the Academy of Nutrition and Dietetics, 2024)

Physicochemical compatibility of caffeine citrate and caffeine base injections with parenteral medications used in neonatal intensive care settings - D. Thisuri N. De Silva; Michael Petrovski; Tobias Strunk; Nabeelah Mukadam; Madhu Page-Sharp; Brioni R. Moore; Kevin T. Batty (European Journal of Clinical Pharmacology, 2024)
Purpose To investigate the physicochemical compatibility of caffeine citrate and caffeine base injections with 43 secondary intravenous (IV) drugs used in Neonatal Intensive Care Unit (NICU) settings. Methods Caffeine citrate (20 mg/mL or 10 mg/mL) or caffeine base injection (10 mg/mL) were mixed in a volume ratio of 1:1 with the secondary drug solution to simulate Y-site co-administration procedures in NICUs. Physical compatibility was evaluated based on visual observation for 2 h, against a black and white background and under polarised light, for changes in colour, precipitation, haze and evolution of gas. Chemical compatibility was determined from caffeine concentration measurements, using a validated high-performance liquid chromatography assay. Results Six of the 43 secondary drugs tested (aciclovir, amphotericin (liposomal), furosemide, hydrocortisone, ibuprofen and ibuprofen lysine) were physically incompatible with caffeine citrate undiluted injection (20 mg/mL), at their high-end, clinically relevant concentrations for NICU settings. However, when tested at lower concentrations, hydrocortisone (1 mg/mL) was physicochemically compatible, whereas furosemide (0.2 mg/mL) was physically incompatible with caffeine citrate. The six drugs which showed physical incompatibility with caffeine citrate 20 mg/mL injection were also physically incompatible with caffeine citrate 10 mg/mL solution. All 43 secondary drugs tested were physicochemically compatible with caffeine base injection. Conclusions Most secondary test drugs, except aciclovir, amphotericin (liposomal), furosemide, hydrocortisone, ibuprofen and ibuprofen lysine, were physicochemically compatible with caffeine citrate injection. Caffeine base injection was physicochemically compatible with all 43 test drugs tested.

Implications and impacts of aligning regional agriculture with a healthy diet - Ryan T. Sharp; Angelina Sanderson Bellamy; Adrian Clear; Samantha Mitchell Finnigan; Ella Furness; Elliot Meador; Helen Metcalfe; Susanna Mills; Kevin Coleman; Andrew P. Whitmore; Alice E. Milne (Journal of Cleaner Production, 2024)

Estimating Ascophyllum nodosum (L.) Le Jolis harvesting impacts using GPS Tracking of mechanical harvesters in Nova Scotia, Canada - Glyn J Sharp; Joshua T Sharp (Journal of Applied Phycology, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics of bacterial blight disease in resistant and susceptible rice varieties - Jennifer T. Niones; Ryan T. Sharp; Dindo King M. Donayre; Eula Gems M. Oreiro; Alice E. Milne; Ricardo Oliva (European Journal of Plant Pathology, 2022)
Bacterial blight ( X. oryzae pv. oryzae ) is a serious disease in rice across the world. To better control the disease, it is important to understand its epidemiology and how key aspects of this (e.g. infection efficiency, and spatial spread) change according to environment (e.g. local site conditions and season), management, and in particular, variety resistance. To explore this, we analysed data on the disease progress on resistant and susceptible varieties of rice grown at four sites in the Philippines across five seasons using a combination of mechanistic modelling and statistical analysis. Disease incidence was generally lower in the resistant variety. However, we found no evidence that the primary infection efficiency was lower in resistant varieties, suggesting that differences were largely due to reduced secondary spread. Despite secondary spread being attributed to splash dispersal which is exacerbated by wind and rain, the wetter sites of Pila and Victoria in south Luzon tended to have lower infection rates than the drier sites in central Luzon. Likewise, we found spread in the dry season can be substantial and should therefore not be ignored. In fact, we found site to be a greater determinant of the number of infection attempts suggesting that other environmental and management factors had greater effect on the disease than climate. Primary infection was characterised by spatially-random observations of disease incidence. As the season progressed, we observed an emerging short-range (1.6 m–4 m) spatial structure suggesting secondary spread was predominantly short-range, particularly where the resistant variety was grown.

Correction to: Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)

Histamine, mast cell tryptase and post-exercise hypotension in healthy and collapsed marathon runners - I. T. Parsons; M. J. Stacey; L. Faconti; N. Hill; J. O’Hara; E. Walter; B. Farukh; R. McNally; H. Sharp; A. Patten; R. Grimaldi; N. Gall; et al. (European Journal of Applied Physiology, 2021)
Purpose Heat stress exacerbates post-exercise hypotension (PEH) and cardiovascular disturbances from elevated body temperature may contribute to exertion-related incapacity. Mast cell degranulation and muscle mass are possible modifiers, though these hypotheses lack practical evidence. This study had three aims: (1) to characterise pre–post-responses in histamine and mast cell tryptase (MCT), (2) to investigate relationships between whole body muscle mass (WBMM) and changes in blood pressure post-marathon, (3) to identify any differences in incapacitated runners. Methods 24 recreational runners were recruited and successfully completed the 2019 Brighton Marathon (COMPLETION). WBMM was measured at baseline. A further eight participants were recruited from incapacitated runners (COLLAPSE). Histamine, MCT, blood pressure, heart rate, body temperature and echocardiographic measures were taken before and after exercise (COMPLETION) and upon incapacitation (COLLAPSE). Results In completion, MCT increased by nearly 50% from baseline ( p = 0.0049), whereas histamine and body temperature did not vary ( p > 0.946). Systolic (SBP), diastolic (DBP) and mean (MAP) arterial blood pressures and systemic vascular resistance (SVR) declined ( p < 0.019). WBMM negatively correlated with $$Δ $$ Δ SBP ( r = − 0.43, p = 0.046). For collapse versus completion, there were significant elevations in MCT (1.77 ± 0.25 μg/L vs 1.18 ± 0.43 μg/L, p = 0.001) and body temperature (39.8 ± 1.3 °C vs 36.2 ± 0.8 °C, p < 0.0001) with a non-significant rise in histamine (9.6 ± 17.9 μg/L vs 13.7 ± 33.9 μg/L, p = 0.107) and significantly lower MAP, DBP and SVR ( p < 0.033). Conclusion These data support the hypothesis that mast cell degranulation is a vasodilatory mechanism underlying PEH and exercise associated collapse. The magnitude of PEH is inversely proportional to the muscle mass and enhanced by concomitant body heating.

Modulation of heroin intake by ovarian hormones in gonadectomized and intact female rats - Mark A. Smith; Sarah B. Ethridge; Tallia Pearson; Huailin Zhang; Madison M. Marcus; Shannon L. Ballard; Alexander T. Casimir; Kenzie M. Potter; Karl T. Schmidt; Jessica L. Sharp; Andrea M. Robinson (Psychopharmacology, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

Longitudinal Variation in Rock Climbing Impacts in the Red River Gorge Area of the Daniel Boone National Forest - Dani T Dagan; Ryan L Sharp; Nicholas Walendziak (Journal of Forestry, 2019)

The Regulation of Monoamine Oxidase A Gene Expression by Distinct Variable Number Tandem Repeats - Maurizio Manca; Veridiana Pessoa; Ana Illera Lopez; Patrick T. Harrison; Fabio Miyajima; Helen Sharp; Andrew Pickles; Jonathan Hill; Chris Murgatroyd; Vivien J. Bubb; John P. Quinn (Journal of Molecular Neuroscience, 2018)

Phosphodiesterase 4 inhibition affects both the direct and indirect pathway: an electrophysiological study examining the tri-phasic response in the substantia nigra pars reticulata - P. R. A. Heckman; J. V. Schweimer; T. Sharp; J. Prickaerts; A. Blokland (Brain Structure and Function, 2018)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

The carbon fertilization effect over a century of anthropogenic CO 2 emissions: higher intracellular CO 2 and more drought resistance among invasive and native grass species contrasts with increased water use efficiency for woody plants in the US Southwest - Brandon L. Drake; David T. Hanson; Timothy K. Lowrey; Zachary D. Sharp (Global Change Biology, 2017)
From 1890 to 2015, anthropogenic carbon dioxide emissions have increased atmospheric CO 2 concentrations from 270 to 400 mol mol −1 . The effect of increased carbon emissions on plant growth and reproduction has been the subject of study of free‐air CO 2 enrichment ( FACE ) experiments. These experiments have found (i) an increase in internal CO 2 partial pressure ( c i ) alongside acclimation of photosynthetic capacity, (ii) variable decreases in stomatal conductance, and (iii) that increases in yield do not increase commensurate with CO 2 concentrations. Our data set, which includes a 115‐year‐long selection of grasses collected in New Mexico since 1892, is consistent with an increased c i as a response to historical CO 2 increase in the atmosphere, with invasive species showing the largest increase. Comparison with Palmer Drought Sensitivity Index ( PDSI ) for New Mexico indicates a moderate correlation with Δ 13 C ( r 2 = 0.32, P r 2 = 0.00, P = 0.91) after 1950. These results indicate that increased c i may have conferred some drought resistance to these grasses through increased availability of CO 2 in the event of reduced stomatal conductance in response to short‐term water shortage. Comparison with C 3 trees from arid environments ( Pinus longaeva and Pinus edulis in the US Southwest) as well as from wetter environments ( Bromus and Poa grasses in New Mexico) suggests differing responses based on environment; arid environments in New Mexico see increased intrinsic water use efficiency ( WUE ) in response to historic elevated CO 2 while wetter environments see increased c i . This study suggests that (i) the observed increases in c i in FACE experiments are consistent with historical CO 2 increases and (ii) the CO 2 increase influences plant sensitivity to water shortage, through either increased WUE or c i in arid and wet environments, respectively.

Molecular variability and phylogenetic relationships of guava (Psidium guajava L.) cultivars using inter-primer binding site (iPBS) and microsatellite (SSR) markers - A. Mehmood; S. Luo; N. M. Ahmad; C. Dong; T. Mahmood; Y. Sajjad; M. J. Jaskani; P. Sharp (Genetic Resources and Crop Evolution, 2016)

A comparison of postrelease survival parameters between single and mass stranded delphinids from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Charles T. Harry; Jane M. Hoppe; Kathleen M. Moore; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; Scott Landry; Jessica Richardson; Michael J. Moore (Marine Mammal Science, 2016)
The viability of healthy single stranded dolphins as immediate release candidates has received little attention. Responders have been reluctant to release lone delphinids due to their social needs, even when they pass the same health evaluations as mass stranded animals. This study tracked postrelease success of 34 relocated and released satellite tagged delphinids from single and mass strandings. Three postrelease survival parameters (transmission duration, swim speed, and daily distance) were examined to evaluate whether they differed among single stranded/single released ( SS / SR ), mass stranded/single released ( MS / SR ), or mass stranded/mass released ( MS / MR ) dolphin groups. Comparisons were also made between healthy and borderline release candidates. Satellite tags transmitted for a mean of 21.2 d ( SD = 19.2, range = 1–79), daily distance traveled was 42.0 km/d (11.25, 20.96–70.72), and swim speed was 4.3 km/h (1.1, 2.15–8.54). Postrelease parameters did not differ between health status groups, however, SS / SR dolphins transmitted for a shorter mean duration than MS / MR and MS / SR groups. Postrelease vessel‐based surveys confirmed conspecific group location for two healthy, MS / SR dolphins. Overall, these results support the potential to release healthy stranded single delphinids; however, further refinement of health assessment protocols for these challenging cases is needed.

Fairway patch - a serious emerging disease of couch (syn. bermudagrass) [Cynodon dactylon] and kikuyu (Pennisetum clandestinum) turf in Australia caused by Phialocephala bamuru P.T.W. Wong & C. Dong sp. nov. - P. T. W. Wong; C. Dong; P. M. Martin; P. J. Sharp (Australasian Plant Pathology, 2015)

Overexpression of AtDREB1D transcription factor improves drought tolerance in soybean - Satish K. Guttikonda; Babu Valliyodan; Anjanasree K. Neelakandan; Lam-Son Phan Tran; Rajesh Kumar; Truyen N. Quach; Priyamvada Voothuluru; Juan J. Gutierrez-Gonzalez; Donavan L. Aldrich; Stephen G. Pallardy; Robert E. Sharp; Tuan-Hua David Ho; et al. (Molecular Biology Reports, 2014)

Hematological, biochemical, and morphological parameters as prognostic indicators for stranded common dolphins ( Delphinus delphis) from Cape Cod, Massachusetts, U.S.A. - Sarah M. Sharp; Joyce S. Knoll; Michael J. Moore; Kathleen M. Moore; Charles T. Harry; Jane M. Hoppe; Misty E. Niemeyer; Ian Robinson; Kathryn S. Rose; W. Brian Sharp; David Rotstein (Marine Mammal Science, 2014)
The current paucity of published blood values and other clinically relevant data for short‐beaked common dolphins, Delphinus delphis, hinders the ability of veterinarians and responders to make well‐informed diagnoses and disposition decisions regarding live strandings of this species. This study examined hematologic, clinical chemistry, and physical parameters from 26 stranded common dolphins on Cape Cod, Massachusetts, in light of their postrelease survival data to evaluate each parameter's efficacy as a prognostic indicator. Statistically and clinically significant differences were found between failed and survived dolphins, including lower hematocrit, hemoglobin, TCO 2 , and bicarbonate and higher blood urea nitrogen, uric acid, and length‐to‐girth ratios in animals that failed. In general when compared to survivors, failed dolphins exhibited acidosis, dehydration, lower PCV s, and decreased body condition. Additionally, failed dolphins had the highest ALT , AST , CK , LDH , GGT , and lactate values. These blood values combined with necropsy findings indicate that there are likely a variety of factors affecting postrelease survival, including both preexisting illness and stranding‐induced conditions such as capture myopathy. Closer evaluation of these parameters for stranded common dolphins on point of care analyzers in the field may allow stranding personnel to make better disposition decisions in the future.

Maximizing information from space data resources: a case for expanding integration across research disciplines - Nandu Goswami; Jerry J. Batzel; Gilles Clément; T. Peter Stein; Alan R. Hargens; M. Keith Sharp; Andrew P. Blaber; Peter G. Roma; Helmut G. Hinghofer-Szalkay (European Journal of Applied Physiology, 2013)

Gene Expression Profiling of Blood in Brain Arteriovenous Malformation Patients - Shantel M. Weinsheimer; Huichun Xu; Achal S. Achrol; Boryana Stamova; Charles E. McCulloch; Ludmila Pawlikowska; Yingfang Tian; Nerissa U. Ko; Michael T. Lawton; Gary K. Steinberg; Steven D. Chang; Glen Jickling; et al. (Translational Stroke Research, 2011)

The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (Ambio, 2011)

Influence of age, sex, and aerobic capacity on forearm and skin blood flow and vascular conductance - Gary J. Hodges; Lisa Sharp; Richard E. Clements; David F. Goldspink; Keith P. George; Nigel T. Cable (European Journal of Applied Physiology, 2010)

Mice overexpressing the 5-hydroxytryptamine transporter show no alterations in feeding behaviour and increased non-feeding responses to fenfluramine - A. Pringle; K. A. Jennings; S. Line; D. M. Bannerman; S. Higgs; T. Sharp (Psychopharmacology, 2008)

CNTO 95, a fully human anti αv integrin antibody, inhibits cell signaling, migration, invasion, and spontaneous metastasis of human breast cancer cells - Qiming Chen; Carol D. Manning; Hillary Millar; Francis L. McCabe; Catherine Ferrante; Celia Sharp; Lillian Shahied-Arruda; Parul Doshi; Marian T. Nakada; G. Mark Anderson (Clinical & Experimental Metastasis, 2008)

Kinetic Modeling of Contrast-Enhanced MRI: An Automated Technique for Assessing Inflammation in the Rheumatoid Arthritis Wrist - Matthew L. Zierhut; Jill C. Gardner; Mary E. Spilker; John T. Sharp; Paolo Vicini (Annals of Biomedical Engineering, 2007)

Identification and imaging of soil and soil-pile deformation in the presence of liquefaction - M. Zeghal; P. V. Kallou; C. Oskay; T. Abdoun; M. K. Sharp (Earthquake Engineering and Engineering Vibration, 2006)

Differential involvement of serotonin and dopamine systems in cost-benefit decisions about delay or effort - F. Denk; M. E. Walton; K. A. Jennings; T. Sharp; M. F. S. Rushworth; D. M. Bannerman (Psychopharmacology, 2005)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

Fasting differentially regulates expression of agouti-related peptide, pro-opiomelanocortin, prepro-orexin, and vasoactive intestinal polypeptide mRNAs in the hypothalamus of Japanese quail - D. Phillips-Singh; Q. Li; S. Takeuchi; T. Ohkubo; P. J. Sharp; T. Boswell (Cell and Tissue Research, 2003)

Metazoan parasites of yellowtail kingfish, Seriola lalandi lalandi , in New Zealand: Prevalence, intensity, and site preference - N. J. Sharp; C. W. Poortenaar; B. K. Diggles; T. J. Willis (New Zealand Journal of Marine and Freshwater Research, 2003)
The prevalence and intensity of metazoan ectoparasites on the skin and gills of kingfish, Seriola lalandi lalandi (Carangidae), collected from White Island (n = 32), Ranfurly Banks (n = 7), and Three Kings Islands (n = 7), is reported. Kingfish were host to two monogenean and four copepod ectoparasite species, Benedenia seriolae, Zeuxapta seriolae, Caligus lalandei, Caligus aesopus, Neobrachiella spp., and Lernanthropus spp., respectively. B. seriolae and C. lalandei infect the skin, whereas the remaining parasites were located on the gills. All parasites exhibited considerable variability in the prevalence and intensity of infection. A few kingfish were completely devoid of C. aesopus, Neobrachiella spp., and/or Lernanthropus spp., whereas others were infected by moderate numbers of these species. However, all kingfish were infected by B. seriolae and Z. seriolae . Therefore, it appears that acclimation of wild kingfish from the east coast of New Zealand's North Island into captivity will lead to the transfer of both B. seriolae and Z. seriolae , and that effective quarantine measures will be required to avoid introducing these parasites into broodstock systems. The site preferences of B. seriolae, Z. seriolae , and C. aesopus were also investigated. B. seriolae exhibited a preference for attachment on the lateral surfaces of the skin behind the dorsal fin, but forward of the anal fin. Z. seriolae displayed a preference for attachment on gill arches 2 and 3, particularly in gill filaments located in the upper regions of the buccal cavity. C. aesopus most commonly occurred on the gill arch.

Numerical Simulation of the Influence of Gravity and Posture on Cardiac Performance - Kristy Peterson; Edwin T. Ozawa; George M. Pantalos; M. Keith Sharp (Annals of Biomedical Engineering, 2002)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Effect of a tyrosine-free amino acid mixture on regional brain catecholamine synthesis and release - Sarah F. B. McTavish; Philip J. Cowen; T. Sharp (Psychopharmacology, 1999)

Effect of antidepressant drugs on dopamine D 1 and D 2 receptor expression and dopamine release in the nucleus accumbens of the rat - K. Ainsworth; S. E. Smith; T. S. C. Zetterström; Q. Pei; M. Franklin; T. Sharp (Psychopharmacology, 1998)

Large angle convergent beam electron diffraction determinations of dislocation Burgers vectors in synthetic stishovite - P. Cordier; T. G. Sharp (Physics and Chemistry of Minerals, 1998)

Electron-beam induced amorphization of stishovite: Silicon-coordination change observed using Si K -edge extended electron energy-loss fine structure - P. A. van Aken; T. G. Sharp; F. Seifert (Physics and Chemistry of Minerals, 1998)

ELNES spectroscopy of mixed Si coordination minerals - B. Poe; F. Seifert; T. Sharp; Z. Wu (Physics and Chemistry of Minerals, 1997)

Enhancement of dopamine-mediated behaviour by the NMDA antagonists MK-801 and CPP: similarities with repeated electroconvulsive shock - S. E. Smith; L. Acton; T. Sharp (Psychopharmacology, 1997)

Evidence that the enhancement of dopamine function by repeated electroconvulsive shock requires concomitant activation of D 1 -like and D 2 -like dopamine receptors - S. E. Smith; T. Sharp (Psychopharmacology, 1997)

The cubic-tetragonal phase transition in the system majorite (Mg 4 Si 4 O 12 ) - pyrope (Mg 3 Al 2 Si 3 O 12 ), and garnet symmetry in the Earth's transition zone - S. Heinemann; T. G. Sharp; F. Seifert; D. C. Rubie (Physics and Chemistry of Minerals, 1997)

Increase of 5-HT 7 (serotonin-7) and 5-HT 1A (serotonin-1A) receptor mRNA expression in rat hippocampus after adrenalectomy - S. Le Corre; T. Sharp; A. H. Young; P. J. Harrison (Psychopharmacology, 1997)

Inhibition of 5-HT cell firing in the DRN by non-selective 5-HT reuptake inhibitors: studies on the role of 5-HT 1A autoreceptors and noradrenergic mechanisms - S. E. Gartside; V. Umbers; T. Sharp (Psychopharmacology, 1997)

Influenza infection in humans and pigs in southeastern China - N. Zhou; S. He; T. Zhang; W. Zou; L. Shu; G. B. Sharp; R. G. Webster (Archives of Virology, 1996)